Electrochemotherapy in Breast Cancer: A Review of References - Schmidt, G.; Juhasz-Böss, I.; Solomayer, E.-F.; Herr, D. (Geburtshilfe und Frauenheilkunde, 2014)
Electrochemotherapy is a new method for the local treatment of cutaneous and subcutaneous metastases. If surgery and/or radiotherapy are no longer possible, this innovative technology can be used effectively for local tumour control. The minor side effects of the therapy and the low intraoperative duration of treatment make it possible to admit patients to hospital for just a short time. Thus, the repeated use of electrochemotherapy has allowed for an increase in the rate of complete remissions. In fact, in 2013, this form of treatment, which consists of a low-dose cytostatic and electroporation, was also included in the mammary guidelines of the Working Group for Gynaecological Oncology (AGO) and the German Cancer Society (DKG). The favourable cost-benefit ratio makes this method of treatment very interesting in clinical practice and, as a result, it is already being used successfully in many German hospitals.
Keywords: breast cancer; metastasis; mammary